Implementasi Sistem Informasi Manajemen Repository Portfolio Berbasis Web untuk Optimalisasi Proses Penilaian Kinerja Dosen di Perguruan Tinggi - Widiantoro, Suryo; Theophilia, Geona (LPPM Universitas Putera Batam, 2024)
The assessment of faculty performance is a mandatory practice for higher education institutions to monitor and maintain the quality of their operations. This is because the quality of a university is partly determined by faculty performance, which includes outputs related to tridharma activities of higher education institutions (teaching, research, and community service), as well as supporting activities. The issue at hand is the absence of a system at the faculty level that can store and manage all faculty activities in the form of reports and documentation of academic and non-academic activities, which are essential for evaluating faculty performance. This study aims to implement a web-based information system to facilitate structured and organized management of faculty activity portfolios. The information system was practically developed using the Laravel framework, with a system development life cycle methodology for its conceptual design. The programming language used for development is PHP, with data storage relying on the capabilities of MySQL for practical reasons. System design is approached using object-oriented methods, with UML serving as the primary analytical tool. The outcome of the study is a web-based application that can be widely accessed via a browser, enhancing user accessibility. Testing was conducted through system integration and user acceptance tests to ensure that the system meets the desired operational conditions. In conclusion, this system represents a digital transformation tool for faculty performance assessment processes, effectively and efficiently facilitating the tasks of faculty members in reporting and documenting their activities, thereby contributing to the improvement of university quality